2023
DOI: 10.1055/s-0042-1758655
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 Inhibition Suppresses Proinflammatory Platelet–Monocyte Interactions

Abstract: Background Monocyte–platelet aggregates (MPAs) represent the crossroads between thrombosis and inflammation, and targeting this axis may suppress thromboinflammation. While antiplatelet therapy (APT) reduces platelet–platelet aggregation and thrombosis, its effects on MPA and platelet effector properties on monocytes are uncertain. Objectives To analyze the effect of platelets on monocyte activation and APT on MPA and platelet-induced monocyte activation. Methods Agonist-stimulated whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…We hypothesized that a focus on antagonism of the P2Y12 receptor pathway alone would be beneficial in patients with COVID-19 by modulating not only platelet aggregation and thrombosis but also platelet-mediated inflammation. 22,23 As such, the ACTIV-4a platform focused antiplatelet investigations on potent P2Y12 inhibitors and specifically ticagrelor. Contrary to our hypothesis, we found no benefit in critically ill and noncritically ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that a focus on antagonism of the P2Y12 receptor pathway alone would be beneficial in patients with COVID-19 by modulating not only platelet aggregation and thrombosis but also platelet-mediated inflammation. 22,23 As such, the ACTIV-4a platform focused antiplatelet investigations on potent P2Y12 inhibitors and specifically ticagrelor. Contrary to our hypothesis, we found no benefit in critically ill and noncritically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of demonstrable benefit of antiplatelet therapies in patients hospitalized for COVID-19 in previous trials could be partially explained by the testing of platelet inhibitors of multiple pathways (aspirin and P2Y12 inhibitors). We hypothesized that a focus on antagonism of the P2Y12 receptor pathway alone would be beneficial in patients with COVID-19 by modulating not only platelet aggregation and thrombosis but also platelet-mediated inflammation . As such, the ACTIV-4a platform focused antiplatelet investigations on potent P2Y12 inhibitors and specifically ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
“…A direct link between P2Y 12 and thrombo-inflammation has recently been reported [40 ▪ ]. Rolling et al [40 ▪ ] showed that ex-vivo incubation of platelets with P2Y 12 inhibitors reduced platelet-induced monocyte recruitment toward a proinflammatory profile, changes in the transcriptome, and thus the formation of monocyte-platelet aggregates (MPAs).…”
Section: Do Mirnas Regulate Cells Involved In Thrombo-inflammation?mentioning
confidence: 99%
“…A direct link between P2Y 12 and thrombo-inflammation has recently been reported [40 ▪ ]. Rolling et al [40 ▪ ] showed that ex-vivo incubation of platelets with P2Y 12 inhibitors reduced platelet-induced monocyte recruitment toward a proinflammatory profile, changes in the transcriptome, and thus the formation of monocyte-platelet aggregates (MPAs). Several studies have demonstrated the regulation of P2Y 12 by miRNAs [41,42], and the association between miR-223 and miR-126 levels and platelet function in patients with acute coronary syndrome [42].…”
Section: Do Mirnas Regulate Cells Involved In Thrombo-inflammation?mentioning
confidence: 99%
See 1 more Smart Citation